On two-field NURBS-based isogeometric formulation for incompressible media problems - Loc, Tran Vinh; Chien, Thai Hoang; Hung, Nguyen Xuan (Vietnam Journal of Mechanics, 2013)
This paper presents u-p mixed formulation relied on the framework of NURBS-based Isogeometric approach (IgA) for incompressible problems. In mixed method, displacement (velocity) field is approximated using NURBS basis functions with one order higher than that of pressure one. Being different from the standard FEM, the IgA allows to increase (or decrease) easily the order and continuous derivative of interpolated functions. As a result, a family of NURBS elements, which satisfies the inf-supcondition, is obtained. Benchmark examples are given to validate the excellent performance of the method.